Analysis of The Relationship Between Dupont Ratio and Dividend Policy (Tobit and Logit Regression Analysis Approach) - Neda Nozohoor; Meysam Kaviani (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This paper aims to investigate and analyze the information content of DuPont ratios concerning corporate dividend policy and also seeks to answer whether the components of DuPont ratios are significantly related to management decisions in dividends. Methodology: To achieve the answer to the above question, we selected 84 companies in the capital market of Tehran as statistical samples. The data collected in 10 years between 2010 and 2019 have been considered, and the hypothesis test has been performed by considering the dependent variable of dividends in different forms through Tobit and logit regression analysis. Findings: The results show that the net return on assets (RONA) and its components, i.e., asset turnover (ATO) and profit margin (PM), concerning dividend policy in all models except the model of one-year-ahead change in dividend had informational content. Originality/Value: This study showed that managers and analysts could analyze how dividend decisions are made through information content obtained through DuPont ratios.